Історія дослідження городища скіфського часу Ширяєве - Каравайко, Д.В. (Археологія і давня історія України, 2020)
Стаття присвячена історії досліджень городища Ширяєво. На сьогоднішній день городище Ширяєве — єдине городище скіфського часу в Путивльському Посейм’ї де проводилися та проводяться зараз
цілеспрямовані археологічні дослідження. Роботи
розпочав у повоєнний час Д. Т. Березовець. Рівно
70 років тому археологічні розкопки на пам’ятці
вперше проведела фахівець-скіфолог В. А. Іллінська, 100-річчя від дня народження якої відзначаємо в 2020 р. Shyriaieve is the only one hillfort of the Scythian
time in Putyvl Seym region, where targeted archaeological
research was carried out. The site has known since
the 19th century. The first excavations were carried
out in 1948—1949 by D. T. Berezovets. Unfortunately,
the information content is extremely low. In 1950, the
famous Ukrainian scythologist Varvara Andriivna Illinska,
also worked at the hillfort. A significant area
was investigated, as a result an informative material
was obtained. Possible construction was revealed.
Excavations led by the author have resumed, since
2017. It gave an opportunity to compare the results of
investigations. The proportions of dwellings absolutely
coincided. It is important to note that the contours of
the construction uncovered in 1950 were fixed conditionally.
The furnaces turned out to be identical. Recent
studies have clarified their construction.
A scrupulous researcher V. A. Illinska recorded a
stratigraphic column in five parts of the excavation.
In 2017—19 here were observed three horizons, which
were shown in the drafts in 1950. The assertion by Varvara
Andriivna that the pottery in the upper part of
the cultural layer are homogeneous and not separated
chronologically turned out to be erroneous.
A small excavation trench of 1950, which is almost
not mentioned in the report and ignored in the publication,
is briefly examined. A pyramidal glass pendant
was found there. In my opinion, this fact, allowed
V. A. Illinska suggest the possibility of a functioning of
the settlement in the IV century BCE.
It should be noted that the excavations of 1950 were
carried out at a high level, the conclusions presented
in the article in 1953 are relevant today, and the article
itself for a long time remained the fundamental
work devoted to the sites of the Scythian time of Putyvl
Seym region.
Systematic and permanent studies have been carried
out since 2017. An informative material is obtained
and requires reflection. It is the subject of a
separate article.